The Network of Education Policy Centers - Būdienė, Virginija (Acta Paedagogica Vilnensia, 2005)
The review of activities of Education Policy Centers (EPC) that emerged in the region in the last couple of years addressing the need for independent and information based policy analysis, advocacy for equity, and effective, sustainable solutions in education policy processes.